Ethnic Differences on Cardiac Rhythms and Autonomic Nervous System Responses During a High-Altitude Trek: A Pilot Study Comparing Italian Trekkers to Nepalese Porters - Verratti, Vittore; Tonacci, Alessandro; Bondi, Danilo; Chiavaroli, Annalisa; Ferrante, Claudio; Brunetti, Luigi; Crisafulli, Antonio; Cerretelli, Paolo (Frontiers in Physiology, 2021)
Altitude hypoxia exposure results in increased sympathetic activity and heart rate due several mechanisms. Recent studies have contested the validity of heart rate variability (HRV) analysis on sympathetic activity measurement. But the plethora of HRV metrics may provide meaningful insights, particularly if linked with cardiovascular and autonomic nervous system parameters. However, population-specific nature of HRV and cardiorespiratory response to altitude hypoxia are still missing. Six Italian trekkers and six Nepalese porters completed 300 Km of a Himalayan trek. ECG analysis was conducted at baseline, and before (bBC) and after (aBC) the high-altitude circuit. Urine was collected before and after the expedition in Italians, for assessing catecholamines. Heart rate increased with altitude significantly (p<.001) in the Italian group; systolic (p=.030) and diastolic (p=.012) blood pressure, and mean arterial pressure (p=.004) increased with altitude. Instead, pulse pressure did not change, although the Nepalese group showed lower baseline values than the Italians. As expected, peripheral oxygen saturation decreased with altitude (p<.001), independently of ethnic groups. Nepalese had a higher respiratory rate (p=.007), independent of altitude. The cardiac vagal index increased at altitude, from baseline to bBC (p=.008). Higuchi fractal dimension showed higher basal values in the Nepalese group (p=.041), and a tendency for highest values at bBC. Regarding the urinary catecholamine response, exposure to high altitude increased urinary levels, particularly of norepinephrine (p=.005, d=1.623). Our findings suggest a better cardiovascular resilience of Nepalese group when compared to Italians, which might be due to an intrinsic adaptation to high altitude, resulting from their job.